ELECTRONIC TRAFFIC LAW ENFORCEMENT AND TRAFFIC LAW ENFORCEMENT - Ori Va Malquna; Alfies Sihombing; Yeni Nuraeni (Awang Long Law Review, 2026)
This research is a normative legal study that analyzes the effectiveness of implementing the Electronic Traffic Law Enforcement (ETLE) system in combating traffic and road transport violations (LLAJ) in Indonesia based on Law Number 22 of 2009 and Government Regulation Number 80 of 2012. The study's focus is directed toward the suitability of implementing ETLE with Article 272 of the Road Traffic and Transportation Act (UU LLAJ), which legitimizes the use of electronic equipment as an aid in enforcing traffic laws. The research method used is normative juridical with a legislative and conceptual approach. The research results indicate that the ETLE system is partially effective in improving public compliance with traffic regulations and reducing extortion practices thru technology-based enforcement and electronic evidence. However, the effectiveness of ETLE implementation still faces several obstacles, including limited supporting infrastructure, suboptimal integration of vehicle ownership data, and low public understanding of ETLE procedures. Therefore, it is necessary to strengthen technical regulations, improve infrastructure quality, and optimize public socialization to support the sustainable effectiveness of technology-based traffic law enforcement.